A new deep-water palaemonid shrimp genus and species from the French Antilles, with a new record of Periclimenes milleri Bruce, 1986 (Decapoda: Caridea) - Anker, Arthur; Corbari, Laure (Zootaxa, 2020)
A new genus and species in the caridean shrimp family Palaemonidae is described based on three type specimens collected at a depth range of 208–385 m off Guadeloupe, French Antilles. Zoukaris festivus gen. et sp. nov. shares many characters with several western Atlantic deep-water species currently assigned to Periclimenes Costa, 1844, as well as with the monotypic western Atlantic genus Diapontonia Bruce, 1986 and the Indo-West Pacific genus Echinopericlimenes Marin & Chan, 2014. Zoukaris gen. nov. can be separated from all of them by a unique combination of morphological features, especially the configuration of the dactylus of the ambulatory pereiopods. In addition, Periclimenes milleri Bruce, 1986 is recorded from the French Antilles based on a single specimen, also from Guadeloupe; its colour pattern is illustrated for the first time.